Occupation-Based Measures—An Overview and Discussion - Bernhard Christoph; Britta Matthes; Christian Ebner (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Occupational information is among the most versatile categories of information about a~person available in quantitative data. The goal of this paper is to provide an overview of occupation-based measures in different topic areas. These include not only measures for analyzing social stratification, such as prestige scales, socioeconomic indices and class schemes but also measures of workplace tasks, occupation-specific health risks, gender segregation, and occupational closure.Moreover, as the quality of such data depends on the quality of the underlying occupational information, we also provide an overview of how to collect occupational information in surveys, how to code this information, and how occupational classifications are commonly used. By doing so, we hope to increase researchers' awareness of the potential of occupation-based analyses, as well as their knowledge of how to properly handle such measures in empirical analyses.
Keywords: 300; Occupational classifications; Occupational prestige; Class schemes; Workplace tasks; Occupational closure; Berufsklassifikationen; Berufsprestige; Klassenschemata; Berufliche Tätigkeitsinhalte; Berufliche Schließung